Self control leader model as an answer to overcome the questions of leadership in the era of the revolution 0.5? - Phanny Tandy Kakauhe (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
The quality of human life is getting worse, not better, so humans continue to see how sin grows and develops. The leaders of nations around the world are trying to find solutions to solve all the world's problems. It is suspected that this world chaos can be resolved by the emergence of an influential leader in a group that is active in society. Leaders must have the ability to make plans, carry out plans, and decide what is necessary. This study uses content analysis, in which the analysis records symbols or messages systematically and then interprets them. As a result, self-control or self-control is an attitude, action, or behavior of a person that is consciously planned or unplanned. One of the very basic characteristics that are significant is the character of self-control, social mastery, and religion. Self-control is influenced by several factors, namely internal factors and external factors. Self-control of a leader greatly affects leadership competence. self-control model by giving the term coercive style leadership model to act when very urgent and important situations occur, crises and panics occur, everything is out of control. The self-control leadership model that works in detail and holistically can make useful decisions and actions.